IMPLIKASI IDEOLOGI TRADISI TATA LINGGIH DALAM PELAKSANAN UPACARA DEWA YAJNA DI DESA PAKRAMAN BANYUNING KABUPATEN BULELENG - Nyoman Suardika (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2018)
This Tata Linggih tradition must be carried out the culmination of the Dewa ceremonyin the village of Pakraman banyuning. Because, this tradition is proof of the success or failure ofthe implementation of the Yajna. The characteristic of this tradition is the revelation or advicefrom the couples who are possessed or possessed by the gods who explain the meaning of theimplementation of this Tradition, purpose, and meaning and explain all the problems that occurin a family that carries out this tradition or the entire Banyuning village community if at theemple owned by the Banyuning village. The implementation of the Tata Linggih tradition mustbe carried out at the peak of the Dewa ceremony in the village of Pakraman banyuning. Because,this tradition is proof of the success or failure of the implementation of the Yajna. The characteristicof this tradition is the revelation or advice from the couples who are possessed or possessed bythe gods who explain the meaning of the implementation of this Tradition, purpose, and meaningand explain all the problems that occur in a family that carries out this tradition or the entireBanyuning village community if at the temple owned by the Banyuning village. Of course thistradition is very interesting because as a medium to communicate with God and the gods invarious social and religious problems in the village of Pakraman Banyuing.Keywords: Implications, Ideology, Tata Linggih Traditions